Impact of Knowledge Management in Supply Chain of Creative Industry - Yanti Mayasari Ginting; Elfindri Elfindri; Hafiz Rahman; Dodi Devianto (International Journal of Supply Chain Management, 2020)
Abstract- In Indonesia, creative economies are deemed as the alternative answers to difficulties facing stiff competition mainly brought by the technological revolution. This paper aims to contribute to the debate on the role of knowledge management (KM) in supply chain management. In this research literature focusing on the application of a KM in the supply chain system for creative industry in Indonesia presented. Results showed that KM is a commercial process that is allied to the production of new information and guaranteeing the espousal of the created knowledge in the company whenever it is needed. KM processes facilitate heightened organizational productivity, innovation, customer satisfaction, and enhanced productivity/process improvement in the supply chain context. The above business sustainability variables rely heavily on the capacity of creative workers to share knowledge, traditions, and experiences. Nonetheless, individuals in the creative world are inclined to hoard or hid knowledge for fear of knowledge risk and loss of livelihood. As a result, professional service firms (PSFs) should embrace. Recommendation of adopting nondisclosure or trade secrets’ contracts, patents, and trademarks to prevent creative staff from practicing knowledge hiding and knowledge hoarding, and consequently, promote knowledge sharing.